Audit of Ten Years of Donation after Circulatory Death Experience in Queensland: Observations of Agonal Physiology following Withdrawal of Cardiorespiratory Support. Issue 4 (July 2018) - Cook, D. A.; Widdicombe, N.
An audit of ten years' experience in all patients undergoing withdrawal of cardiorespiratory support (WCRS) in the context of donation after circulatory death (DCD) was conducted in Queensland, Australia (2008 to 2017). One hundred and seventy-one patients proceeded to donation after declaration of death by circulatory criteria with loss of pulsatile arterial blood pressure (circulatory arrest) for five minutes. The demographics, times and haemodynamic observations were abstracted, de-identified and collated. The average age of patients was 43 years (standard deviation 16.1 years) and 63% were male. The median and mean times to an agonal systolic blood pressure below 50 mmHg were 10 and 11 minutes and the median and mean times from WCRS to circulatory arrest were 14 and 16 minutes. After systolic blood pressure fell to 50 mmHg or lower, 33 patients (19.3%) had spontaneous return of systolic pressure to above 50 mmHg. Following periods of circulatory arrest, five patients were documented to have spontaneous return of pulsatile arterial pressure. Two patients had return of circulation after two minutes, but less than five minutes of circulatory arrest and three patients had return of circulation where circulatory arrest had been documented for less than two minutes. Following WCRS, transient restoration of circulation following circulatory arrest may occur, even following two minutes of circulatory asystole, albeit rarely.